Intertextuality Analysis in Narada Short Story by Y.B. Mangunwijaya - Umu Hana Amini (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2024)
Literary works are born from the thoughts of authors who are influenced by other texts. No text stands alone. So, of course there is a connection between a text which in this case is a literary work with other texts. What is meant by text is not always in the form of writing, but also includes oral texts and ideas that influence the author. A work can be known hypogram and its relation or intertextuality with other texts by intertextual analysis. This study discusses intertextuality in Y. B. Mangunwijaya's short story Narada by using Julia Kristeva's intertextuality theory approach. This research is a qualitative research with data collection techniques with the method of observing and taking notes. The data was obtained from Narada's short story in the form of phrases/sentences containing intertextuality and sourced from Y. B. Mangunwijaya's book entitled Rumah Bambu which was published by KPG (Kepustakaan Populer Gramedia) in 2020, the seventh edition. The hypogram of this short story is a wayang (puppet) text whose title is not specifically mentioned because the link or intertextuality is in the form of similarity of characters. In addition to intertextuality in the form of similarities, this short story also contains a modification of ideas by deconstructing the values in the puppet story, showing that the adaptation of the story is adapted to the conditions of the times.